Contextualising Aboriginal faunal stories with the Linnaean taxonomy: Culturally responsive pedagogy in zoology - Joël Rioux; Bronwyn Ewing (The Australian Journal of Indigenous Education, 2022)
This article explores the contextualising of local Aboriginal animal stories with the zoology curriculum in Queensland at one independent high school, where students’ learning potential often remains untapped. Contextualisation, encompasses heritage, cultural knowledge, country and Linnaean zoology taxonomy to form a culturally responsive pedagogy that supports students’ learning and pride in their heritage. To illustrate how students can learn in culturally responsive ways, a sinuous path encompassing six phases for collecting local faunal stories was necessary, prior to delivering the Linnaean zoology taxonomy. Elders’ animal stories were documented and then contextualised into classificatory materials to integrate local faunal knowledge. Drawing on an Indigenist Research Framework including storytelling, talking circles, interviewing and Action Research methodology, transcribing, retranscribing and restorying was used to explore the effect of a culturally responsive approach on students’ culture, and knowledge of local fauna. Findings indicated that the local animal stories became the foundation for the development of a First Classification of Animal Kingdom chart from the non-Aboriginal animal knowledge tradition which tapped into students’ learning potential through elders’ stories about local culture. Real-life storytelling on country is preferable as such contexts provide meaningful learning for students, rather than in decontextualised classroom spaces.